Chinese health funding in Africa: The untold story. - Carrie B Dolan; Ammar A Malik; Sheng Zhang; Wenhui Mao; Kaci Kennedy McDade; Eli Svoboda; Julius N Odhiambo (Public Library of Science (PLoS), 2023)
The motivations behind China's allocation of health aid to Africa remain complex due to limited information on the details of health aid project activities. Insufficient knowledge about the purpose of China's health aid hinders our understanding of China's comprehensive role in supporting Africa's healthcare system. To address this gap, our study aimed to gain better insights into China's health aid priorities and the factors driving these priorities across Africa. To achieve this, we utilized AidData's Chinese Official Finance Dataset and adhered to the Organisation for Economic Co-operation and Development (OECD) guidelines. We reclassified all 1,026 health projects in Africa, originally categorized under broad 3-digit OECD-DAC sector codes, into more specific 5-digit CRS codes. By analyzing the project count and financial value, we assessed the shifting priorities over time. Our analysis revealed that China's priorities in health aid have evolved between 2000 and 2017. In the early 2000s, China primarily allocated aid to basic health personnel and lacked diversity in sub-sectors. However, after 2004, China shifted its focus more toward basic infrastructure and reduced emphasis on clinical-level staff. Furthermore, China's interest in addressing malaria expanded both in scale and depth between 2006 and 2009. This trend continued in 2012 and 2014 when China responded to the Ebola outbreak by shifting its focus from basic infrastructure to infectious diseases. In summary, our findings demonstrate the changes in China's health aid strategy, starting with addressing diseases already eliminated in China and gradually transitioning towards global health security, health system strengthening, and shaping the governance mechanisms.